Financial settlement modes and corruption: evidence from developed nations - Rajeev K. Goel; Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
Using recent pooled data from several developed nations, the paper uniquely examines whether the composition of payment instruments has a bearing on the prevalence of corruption in a country. Our results suggest that the choice of instruments matters. Paper credit transfer transactions are consis-tently associated with corrupt activities, while credit card transactions tend to reduce them. Cheques generally increase corruption, the results with respect to nonpaper credit transfers are mixed, while direct debits fail to show significant effects on corruption. These findings hold for alternative corruption measures and when allowance is made for endogeneity of payment instruments.
URN:NBN:fi:bof-201408072048
Keywords: K4; G3; H3; F3; 330; Corruption; Cheques; Credit card; Cash; Direct debit; Payment instruments